THE EFFECTS OF BACK EXTENSION TRAINING ON BACK MUSCLE STRENGTH AND SPINAL RANGE OF MOTION IN YOUNG FEMALES - Yıldız Yaprak (Termedia Publishing House, 2013)
The objective of this study was to determine the effects of a 10-week dynamic back extension training programme and its effects on back muscle strength, back muscle endurance and spinal range of motion (ROM) for healthy young females. Seventy-three young females (age: 19.32±1.80 years, height: 158.89±4.71 cm, body weight: 55.67±6.30 kg) volunteered for the study. Prior to the training period, all participants completed anthropometric measurements, back muscle strength and endurance test, lateral bending and spinal ROM measurements. After measurements, the participants were divided into two groups. The exercise group (N:35) performed the dynamic back extension exercise 3 days per week for 10 weeks. The control group (N:38) did not participate in any type of exercise. The mixed design ANOVA (group x time) was used to determine the difference in pre- and post-training values. The present findings show that there were significant differences between pre-training and post-training values for back muscle strength and spinal ROM in the exercise group. Following the dynamic strength training programme, back muscle strength and spine ROM values except flexion of the lumbar 5-sacrum 1 (L5-S1) segment of the exercise group showed a significant increase when compared with the pre test values. The control group did not show any significant changes when compared with the pre-training values. The results demonstrate that the 10-week dynamic strength training programme was effective for spinal extension ROM and back muscle strength, but there was no change in back muscle endurance. In this context, this programme could potentially be used to prevent the decrease of spinal ROM as well as provide an increase in the fitness parameters of healthy individuals.